Fractional variable structure control - Tenreiro Machado, J. A. (2011)
This paper studies fractional order variable structure control algorithms. For that purpose the fractional order of the sliding mode is varied and its effect upon the system performance is evaluated. The test bed is constituted by a simple mechanical manipulator. Both the system response and the control effort are analysed. The results show that the fractional order provides an extra method for adjusting the closed loop system response.